2016
DOI: 10.1002/jbmr.2790
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Mineralization Deficits and Impaired Biogenesis and Function of Chondrocyte-Derived Matrix Vesicles in Phospho1–/– and Phospho1/Pit1 Double-Knockout Mice

Abstract: We have previously shown that ablation of either the Phospho1 or Alpl gene, encoding PHOSPHO1 and tissue-nonspecific alkaline phosphatase (TNAP) respectively, lead to hyperosteoidosis but that their chondrocyte- and osteoblast-derived matrix vesicles (MVs) are able to initiate mineralization. In contrast, the double ablation of Phospho1 and Alpl completely abolish initiation and progression of skeletal mineralization. We argued that MVs initiate mineralization by a dual mechanism: PHOSPHO1-mediated intravesicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…The presence of HA in MV isolated from 17IIA11 cells grown under osteogenic conditions for 8 days was further confirmed by examining MV dropped onto a mica substrate and imaged by means of AFM, followed by qualitative evaluations of their internal composition by AFM phase analysis (56). MV AFM phase images showed the presence of internal spots with high phase angle (φ) values surrounded by regions with very low φ values (Fig.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The presence of HA in MV isolated from 17IIA11 cells grown under osteogenic conditions for 8 days was further confirmed by examining MV dropped onto a mica substrate and imaged by means of AFM, followed by qualitative evaluations of their internal composition by AFM phase analysis (56). MV AFM phase images showed the presence of internal spots with high phase angle (φ) values surrounded by regions with very low φ values (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…To further confirm the MV secreted by 17IIA11 cells are mineralization-competent, we used transmission electron microscopy (TEM) with electron diffraction (54, 55) and atomic force microscopy (AFM) phase analyses (56). In our previous studies we determined that mineralization of 17IIA11 cells ECM is visible around day 5 of culture under osteogenic conditions (4850).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ENPP1 produces PP i as well as P i from adenosine 5 ′ - triphosphate (ATP), while TNAP hydrolyzes both ATP and PP i to form P i [27]. Phosphate transporter 1 (P i T-1) helps incorporate P i into MVs [28, 29] (Fig. 3A), while annexins may be involved in the binding and transport of Ca 2+ and in the biophysical process that initiates mineralization in the MV lumen [30] (Fig.…”
Section: Description Of Mvsmentioning
confidence: 99%
“…Thus, these studies, using an innovative combination of AFM topography and phase imaging, showed that the genetic ablation of PHOSPHO1 impairs MV biogenesis and NC formation. This result, in turn, suggests that the intra-vesicular production of P i is necessary for the correct Ca 2+ /P i stoichiometry for the formation of the NC (Yadav et al 2016).…”
Section: What Are the Biomimetic Systems Of Mvs?mentioning
confidence: 83%